2022
DOI: 10.3389/fvets.2021.796494
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Subclinical Ketosis and Liver Function Test Indices in Adipose Tissues Associated With Hyperketonemia in Postpartum Dairy Cattle

Abstract: Past studies suggested that during early lactation and the transition period, higher plasma growth hormone (GH) levels in subclinical ketosis (SCK) might involve the initiation of body adipose tissues mobilization, resulting in metabolic disorders in ruminants particularly hyperketonemia. The upregulated GH mRNA expression in adipose tissue may take part in the adipolysis process in SCK-affected cows that paves a way for study further. This study aimed to characterize the plasma levels of GH, β-hydroxybutyrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
2
6
0
1
Order By: Relevance
“…Our study observed that ALT levels tended to be higher in cows with SCK compared to CON, suggesting possible liver damage in ketotic cows. These observations align with previous research that has also found elevated levels of AST or ALT in the blood of dairy cows affected by ketosis [76,85,86].…”
Section: Discussionsupporting
confidence: 92%
“…Our study observed that ALT levels tended to be higher in cows with SCK compared to CON, suggesting possible liver damage in ketotic cows. These observations align with previous research that has also found elevated levels of AST or ALT in the blood of dairy cows affected by ketosis [76,85,86].…”
Section: Discussionsupporting
confidence: 92%
“…The occurrence of ketosis is often accompanied by fat deposition in the liver [25]. The essence is that after excess NEFAs (nonesterified fatty acid, fatty acids above C10, mainly VLCFAs) enter the liver, part of NEFAs enter the ketone body synthesis pathway to generate ketone bodies [26,27]. Study showed a greater level of ROS in mammary epithelial cells of ketotic cows, and greater oxidant indices, indicating increased oxidative stress status [28,29].…”
Section: The Significance Of Peroxisomal β-Oxidationmentioning
confidence: 99%
“…The liver is the main organ responsible for synthesizing plasma proteins. 26 TP, ALB and GLO are important indicators of liver function and metabolism in the body. 27 Studies have reported that serum protein levels are positively correlated with the degree of liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the differences in eggshell strength may be related to E2 levels, but a more detailed correlation analysis between E2 levels and eggshell strength at different stages still needs to be conducted in future studies. The liver is the main organ responsible for synthesizing plasma proteins 26 . TP, ALB and GLO are important indicators of liver function and metabolism in the body 27 .…”
Section: Discussionmentioning
confidence: 99%